Las habilidades sociales como estrategia de integración de los estudiantes del colegio “Hernán Gallardo Moscoso” en el año lectivo 2012-2013 - Briceño Veintimilla, Karina Cumandá (2015)
This research includes social skills and strategies for integrating students of the College "Gallardo Hernan Moscoso" in the 2013-2014 school year, the same that seeks to explain the influence of social skills in the integration of students; research is descriptive in nature, the methods used in the fieldwork were: scientific, deductive, inductive, analytic and synthetic. The technique for data collection was the survey through a series of questions targeted at 9 teachers and 180 students on general aspects of social skills. The results of higher percentage are: teachers claim that the educational institution provides students with the facilities for the development of social skills; conceptualize social skills, you should put more emphasis developing basic, advanced skills. It is recommended that research related to social skills and integration strategies, where authorities involving teachers, parents, student council and students, in order to be implemented in code in a coordinated coexistence is made.